Validating fin tissue as a non-lethal proxy to liver and muscle tissue for stable isotope analysis of yellow perch (Perca flavescens). Issue 2 (4th March 2018) - McCloskey, Meagan; Yurkowski, David J.; Semeniuk, Christina A. D.
ABSTRACT: Stable isotope ecology typically involves sacrificing the animal to obtain tissues. However, with threatened species or in long-term longitudinal studies, non-lethal sampling techniques should be used. The objectives of this study were to (1) determine if caudal fin tissue could be used as a non-lethal proxy to liver and muscle for stable isotope analysis, and (2) assess the effects of ethanol preservation on δ 15 N and δ 13 C in fin tissue of juvenile yellow perch Perca flavescens . The δ 13 C of caudal fin was not significantly different from liver ( t 23  = −0.58; p  = 0.57), and was more correlated with δ 15 N in liver ( r 2  = 0.78) than muscle ( r 2  = 0.56). Ethanol preservation enriched 15 N and 13 C for caudal fins, but by using our developed regression models, these changes in δ 15 N and δ 13 C can now be corrected. Overall, caudal fin tissue is a more reliable proxy to liver than muscle for δ 15 N and δ 13 C in yellow perch.